The head position and cervical alignment in patients with Chiari malformation: A retrospective case–control study - Resul Karadeniz; Zeynep Dağlar; Emin Çağıl; Göksal Günerhan; Buse Sarıgül; Yılmaz Aslan; Ahmet Deniz Belen; Ali Dalgıç (Journal of Craniovertebral Junction and Spine)
Aim and Background: This study aimed to investigate the relationship between cervical spinal alignment and the center of gravity (COG) of the head in patients with Chiari malformation (CM) compared to healthy individuals. CM is characterized by the herniation of posterior fossa structures through the foramen magnum, potentially affecting head positioning and craniovertebral junction biomechanics. Understanding these biomechanical changes is crucial for improving diagnostic and treatment strategies. Materials and Methods: This retrospective study included 102 CM patients and 71 healthy controls. Radiological measurements were obtained from cervical X-rays, with seven reference points used to calculate angles related to head positioning and cervical curvature. Angular parameters, including cranial incidence (CI), cranial slope (CS), cranial tilt (CT), C7 slope (C7S), and spinocranial angle (SCA), were analyzed to determine correlations with the COG of the head. Statistical analyses were performed using t-tests, ROC analysis, and Pearson/Spearman correlation tests. Results: CM patients had significantly higher CI, CT, STT, and SCA angles compared to controls (P < 0.05), indicating an anterior displacement of the head’s COG. The CS angle was lower in CM patients (P < 0.05), reflecting a more flexed head position. No significant differences were found in C7S and C2T angles between groups, suggesting similar cervical curvature. ROC analysis demonstrated high sensitivity and specificity of the angular measurements for diagnosing CM. Conclusion: CM patients exhibit distinct biomechanical alterations, including an anterior shift of the COG and a more flexed head position. These findings highlight the potential of angular measurements as noninvasive diagnostic tools for CM. Future studies should explore the implications of these biomechanical changes on CM progression and treatment outcomes.